The Port of Split international marine traffic emissions inventory - Stazić, Ladislav (Array, 2020)
The Port of Split is one of the busiest marine traffic regions in the Adriatic Sea and the third largest passenger port in the Mediterranean. A significant number of the ships is going in and out of the Port, creating a major impact to the environment in the area. That impact is created mostly by emissions from ships, which can be divided into greenhouse gases (predominantly Carbon dioxide – CO2) and the pollutants (Nitrogen oxides – NOX, Sulphur oxides – SOX, Particulate matter – PM and Volatile organic compounds – VOC). This paper is presenting emission inventory of international marine traffic in the Port of Split for the year 2017, which amounts to 19065.8 tons of CO2, 12 tons of SOX, 11.7 tons of PM, 14.6 tons of VOC and 338.7 tons of NOX. Emissions are presented in groups according to type of ships, thus enabling comparison of emissions coming from cargo and passenger traffic. Cruise ships activity in the Port of Split during 2018 is added to the paper to highlight the increase of the traffic and consequently emissions.